An Atlas of Planar and Spect Bone Scans - Fogelman, Ignac; Autor (London, England : Mosby, 1989)
This atlas considers in datail adult bone scanning with, Tc-labelled diphosphonates, and includes a limited selection of isms of tracer uptake and techniques for both planar and spect bone scanning are first described.
Contents 1. Introducción 2. Patterrn recognition 3.Clinical indication for bone scanning: investigation of bone pain 4. Clinical indication for bone scanning: investigation of malignancy 5. Clinical indication for bone scanning: investigation of beningn bone disease Miscellaneous topics
include index
Keywords: lembs -- BONES -- DISEASES; lembs -- BONES -- RADIONUCLIDE IMAGING